Need-based Reproductive Health Care Program in Iranian Surrogate Mothers; A Qualitative Study - Marjan Goli; Shahnaz Kohan; Zeinab Heidari; Ziba Farajzadegan; Seiied Mahdi Ahmadi-Oloonabadi (مجله دانشکده پزشکی اصفهان, 2021)
Background: Surrogate mothers assist infertile couple by caring their baby. Assessments show differences on various aspects of reproductive health matters compared to normative pregnancy. The aim of this study was to develop a reproductive health care program for surrogate mothers.